Linguagem e significado nas investigações filosóficas de Wittgenstein - Tavares, Francisco Renato [UNIFESP] (2019)
This work presents the way in which Wittgenstein understands the language in Philosophical Investigations. From a dialogue with the Augustinian image, the Austrian presents a new form of understanding the language. According to this form, language is understood by the idea of language games that presents the same as an activity that occurs in a context of practices shared by users of language, not for an alleged relationship established between language and world. With the idea of language games, Wittgenstein shows that various forms of linguistic use are possible, not just a single form, and many of the so-called philosophical problems results from a misunderstanding of what linguistic activity is.